Preliminary report: Surgical outcomes following genitoplasty in children with moderate to severe genital atypia. Issue 2 (April 2018) - Bernabé, K.J.; Nokoff, N.J.; Galan, D.; Felsen, D.; Aston, C.E.; Austin, P.; Baskin, L.; Chan, Y.-M.; Cheng, E.Y.; Diamond, D.A.; Ellens, R.; Fried, A.; et al.
Summary: Introduction: Prior studies of outcomes following genitoplasty have reported high rates of surgical complications among children with atypical genitalia. Few studies have prospectively assessed outcomes after contemporary surgical approaches. Objective: The current study reported the occurrence of early postoperative complications and of cosmetic outcomes (as rated by surgeons and parents) at 12 months following contemporary genitoplasty procedures in children born with atypical genitalia. Study design: This 11-site, prospective study included children aged ≤2 years, with Prader 3–5 or Quigley 3–6 external genitalia, with no prior genitoplasty and non-urogenital malformations at the time of enrollment. Genital appearance was rated on a 4-point Likert scale. Paired t -tests evaluated differences in cosmesis ratings. Results: Out of 27 children, 10 were 46, XY patients with the following diagnoses: gonadal dysgenesis, PAIS or testosterone biosynthetic defect, severe hypospadias and microphallus, who were reared male. Sixteen 46, XX congenital adrenal hyperplasia patients were reared female and one child with sex chromosome mosaicism was reared male. Eleven children had masculinizing genitoplasty for penoscrotal or perineal hypospadias (one-stage, three; two-stage, eight). Among one-stage surgeries, one child had meatal stenosis (minor) and one developed both urinary retention (minor) and urethrocutaneous fistula (major) (Summary Figure ). Among two-stage surgeries, three children developed a major complication: penoscrotal fistula, glans dehiscence or urethral dehiscence. Among 16 children who had feminizing genitoplasty, vaginoplasty was performed in all, clitoroplasty in nine, external genitoplasty in 13, urethroplasty in four, perineoplasty in five, and total urogenital sinus mobilization in two. Two children had minor complications: one had a UTI, and one had both a mucosal skin tag and vaginal mucosal polyp. Two additional children developed a major complication: vaginal stenosis. Cosmesis scores revealed sustained improvements from 6 months post-genitoplasty, as previously reported, with all scores reported as good or satisfied. Discussion: In these preliminary data from a multi-site, observational study, parents and surgeons were equally satisfied with the cosmetic outcomes 12 months after genitoplasty. A small number of patients had major complications in both feminizing and masculinizing surgeries; two-stage hypospadias repair had the most major complications. Long-term follow-up of patients at post-puberty will provide a better assessment of outcomes in this population. Conclusion: In this cohort of children with moderate to severe atypical genitalia, preliminary data on both surgical and cosmetic outcomes were presented. Findings from this study, and from following these children in long-term studies, will help guide practitioners in their discussions with families about surgical management. Summary Figure Surgical complications at 12-month postoperative follow-up, n = 27. *Among the six complications in the masculinizing surgery group, one patient developed both urinary retention (minor) and urethrocutaneous fistula (major). ǂ Among the five complications in the feminizing surgery group, one patient had both a mucosal skin tag (minor) and vaginal mucosal polyp (minor).